Budaya Organisasi Transdisipliner - Nurul Oktaviana Mekawati; Herianto Herianto; Fachruddin Azmi; Nurika Khalila Daulay (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Rapid changes in global culture demand that people grow to adapt to science which is now unable to stand up partially. So the transdisciplinary approach is present as an effort to solve current problems. In managing an organization, it is necessary to apply modern management principles that pay attention to organizational culture. There are dynamics within an organization in building organizational culture as a guideline and principle for every individual in an organization in carrying out their respective duties and obligations to achieve organizational goals. This study uses the literature study method which aims to find out the discussion about transdisciplinary organizational culture. The data analysis technique used in this research is content analysis. The results of this study indicate that (1) a transdisciplinary approach is needed in organizational culture that runs in the era of globalization, (2) transdisciplinary implementation in organizational culture implies a process of multidisciplinary integration that is used to discuss issues or deal with global problems in the sustainability of organizational culture. (3) The implementation of transdisciplinary implies the existence of "cooperative" work or synergy between the people involved in it. The synergy in the transdisciplinary concept is intended to achieve organizational goals.